Integration of Sustainable Development Pillars in the RPJPD Document of West Lombok Regency - Syahida, Nidya Putri; Suryaningsih, Suryaningsih (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
The problem that often occurs in planning is the Government's consistency in formulating plans, with accurate data or processes carried out not by applicable regulations, so sustainable development is only normative without any concern for achieving predetermined targets. However, the urgency of sustainable development cannot be overstated. It is an agenda echoed globally and has become the world's attention to resolve the gaps that have occurred so far. The pillars of sustainable development are social, economic, and environmental sustainability. These three pillars are derived into 17 indicators known as SDGS, which help make it easier to evaluate the achievement. This research method uses qualitative methods with data collection carried out both primary and secondary through interviews, observations, and document reviews. This study aimed to determine the integration of the sustainable development pillars in preparing the RPJPD document in West Lombok Regency. The urgency of this research is to find out the readiness and condition of the region to support the country in achieving sustainable development goals. The result of this research is that West Lombok Regency makes sustainable development the basis of long-term development planning (RPJPD).